Surdos incluídos : sujeitos ou assujeitados? - Matias, Wander Luis (2015)
In this thesis deal with the Social Inclusion of people deaf, the influences for the composition of consciousness as a group, of an increase or not of exclusion. From the more than 10 years experience of the author with the deaf community of the city of Uberlândia. The work was arranged with discussions that appear necessary on the Deaf, their trajectories, influences and dreams to detect by \"voices\"2 we seek to identify why these voices exist or not and how they are (IRAM) its formation as people. We deal with Deaf Pounds users - Brazilian Sign Language. We have used new technologies to this approach with the respondents (Whatsapp, Skype, Facebook, Messenger and email). We make a theoretical framework based on Harlan Lane and his book \"The Mask of Benevolence\"- a free translation for A Máscara da Benevolência , the author treat also this public denouncing a hearing acculturation on the deaf and for being the consistent reports with the deaf education in criticism of what takes place in our country - welfare of nature. The choice of this interpretative model follows the lines presented in the text of Harlan Lane (1992), graduated in psychology arguing obscure points, rarely brought up in education, and found that the story goes further. We have used other authors to understand the Deaf and their training. We also analyze the professionals involved in this process: teachers and translators interpreters pounds per relate directly to the theme of deafness and, therefore, steeped in performing a different job. Subsidized for both of previous studies on the subject. We discover and consider that the theory presented by the author Harlan Lane (1992), expanded by Capovilla (2011), Sa (2006) Tables (2006), Fernandes (2011) among others, is still present with regard to the constitution of these people. The education of the deaf, for the most part, allows them to be devoid of will and not subjects. We have used the exploratory research, the one most suited to the work.